Visualisation in popular fiction, 1860 - 1960 graphic narratives, fictional images - Sillars, Stuart 1951- (Taylor and Francis, 2005)
Explores the tradition of illustrated fiction in English, offering new approaches for its study and detailed discussions of a range of representative texts. Of value to students of literature, cultural studies, visual art and film